Popoki, What Color is Peace? Exploring critical approaches to thinking, imagining and expressing peace with the cat, Popoki - Alexander, Ronni (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
The Popoki Peace Project is a celebration of life in all its richness and variation. It uses the cat Popoki as a metaphor for life that is viable and possible, a radical democratic politics which allows for subjects to “performatively assert their right to livable life where there has been no such prior authorization.”1 Begun in Japan in 2006, the Project attempts to address the need to delve into the meaning of peace in a contemporary context and to find new ways of promoting critical thinking, critical imagination and critical expressions of peace. In its work, the Project attempts to create ‘oases of peace,’ non-violent, alternative spaces in which all participants are active partners in celebrating life and diversity, and creating positive peace.